Composition space of PtIrPdRhRu high entropy alloy nanoparticles synthesized by solvothermal reactions. Issue 91 (26th October 2022) - Bertelsen, Andreas Dueholm; Hansen, Alexander Reinhardt; Broge, Nils Lau Nyborg; Mamakhel, Aref; Bondesgaard, Martin; Iversen, Bo Brummerstedt
Abstract : The available composition space of the high entropy alloy PtIrPdRhRu, synthesized under solvothermal conditions, has been explored varying precursor ratios. Abstract : High entropy alloy (HEA) nanoparticles hold promise in heterogeneous catalysis, and recently, simple and benign solvothermal synthesis was achieved for the equimolar PtIrPdRhRu. Here we experimentally explore the available composition space in this system, and we find that single-phase products can be obtained at significant deviations from the equimolar case.